KEEFEKTIFAN MODEL PENEMUAN TERBIMBING DAN COOPERATIVE LEARNING PADA PEMBELAJARAN MATEMATIKA - Yoppy Wahyu Purnomo (Jurnal Kependidikan, 2011)
The purposes of this study are: (1) to find out which between the study models can give the best mathematics learning results; (2) to find out which student creativity categories can give the best mathematics learning result; (3) to find out the interaction between the study models and student creativities towards the results of learning. The results of learning in this case are limited to the subject of Bangun Ruang Sisi Lengkung. The study uses a quasi-experimental design by using two-way analysis of variance with unequal cell sizes. The population of the study refers to all students of Grade IX in the junior high schools in District Area 04 of the Sub-Province of Wonogiri sampled into three classes of two schools through stratified and cluster random sampling. Data are colllected by documentation, questionnaire, and tests. Results of analyses with 0.05 level of significance and continued by double comparation test show: 1) The guided discovery model and cooperative learning give the same learning results but are better than the conventional model. (2) Students with a higher creativity level in mathematics have better results than students with a lower creativity level. (3) At the high creativity category level, students show better results in guided discovery model than cooperative learning and cooperative learning is better than the conventional model. At the low and medium creativity level, guided discovery model and cooperative learning model give the same learning results but better than the conventional model. Besides, in the guided discovery model, students with high creativity level do better than students with medium creativity level and students with medium creativity level have the same results as students with low creativity level. As with the cooperative learning model and conventional model, students with high, medium, and low creativity models show the same learning results